Analisis Rancangan Panel Automatic Transfer Switch and Automatic Main Failure - Irfan Wahyu Ramadhan; Hendra Setiawan; Sisdarmanto Adinandra (Jurnal Serambi Engineering, 2024)
In 2022, electricity consumption in Indonesia will increase significantly, especially in the industrial sector, which is the second largest consumer after households. Interruptions in PLN's power supply can cause industrial equipment and machinery to stop working, resulting in significant losses for the industrial sector. The limitations of manual transfer of backup power sources also contribute to this problem. Therefore, this research aims to develop an automatic control system for a genset. With this approach, it is expected that the power supply can be maintained without interruption, thereby improving efficiency and operational performance. The design integrates an Automatic Transfer Switch (ATS) and Automatic Mains Failure (AMF) system within a single panel framework, following the regulations outlined in Peraturan Menteri ESDM Nomor 11 and Persyaratan Umum Instalasi Listrik Indonesia. The panel design includes technical data identification, circuit design, circuit simulation, component selection, panel box design and final evaluation. Simulations using FluidSIM software help to validate the operation of the panel in various scenarios. The test results conclude that the panel can function as intended, with automatic control of the genset protection system and automatic switching of the power supply to the load. Manual control is also possible to assist operators during genset maintenance and repair